The Stabilization Doctrines of Carl Snyder - Reed, Harold L. (Quarterly Journal of Economics, 1935)
I. The Qualitative vs. the Quantitative Schools of Credit Control, 600. — II. Subgroupings among Exponents of Quantitative Methods, 602. — III. Snyder's Methods, 603. — IV. History of Price Movements, 604. — V. Consequences of Non-War Price Displacements, 606. — VI. Fluctuations in Prices vs. Fluctuations in the Physical Volume of Trade, 606. — VII. Measurement of the Factors of the Equation of Exchange, 609. — VIII. Consequences of Fluctuations in the Ratio of Credit to Trade, 611. — IX. Sub-Normal and Abnormally High Rates of Growth in the Volume of Credit, 613. — X. Does Credit Control Trade? 615.—XI. Snyder's Theory and the 1929 Crash, 616. — XII. Snyder's Theory and the Present Depression, 618. — XIII. Necessity of Frequent Tests of the Credit Situation, 619.